Analytical modeling of armature magnetic field in spoke-type permanent magnet machine considering saturation of magnetic bridge - CHEN Zhenfei; LI Jiayu; FAN Chenyang; LI Zhixin; WANG Qingyan (电力工程技术, 2023)
In order to solve the accurate calculation problem of spoke-type permanent magnet machines with multi-layer winding structure in the magnetic field, based on the two-dimensional subdomain analytical modeling idea, a magnetic density analytical calculation method considering the saturation effect at the rotor magnetic bridge and stator multi-layer winding structure is proposed. In this method, the magnetic vector potential calculation of multi-layer armature winding can be calculated by subdomain division in the stator slot. Then, the saturation effect at the spoke-type rotor core magnetic bridge is equivalent by using an equivalent air gap. To ensure the accuracy of calculation, the error check and cyclic iteration are applied in this method. The key contribution of this method is effectively solving the interior permanent magnet machines′ magnetic field calculation problem in the traditional subdomain modeling method due to the inability to consider the finite magnetic permeability of the core. Taking 8-pole 9-slot and 10-pole 12-slot permanent magnet machines as examples, finite element models with different winding structures are built to validate the validity of the proposed method. The results show that the analytical method achieves a reduction in the computation time while maintaining the calculation accuracy.